Knowledge, Attitude and Practice Regarding Minimal Invasive Dentistry Among General Dental Practitioners in Tamil Nadu - B, RESHMI.; SAKTHI, DR. D. SRI; S, DR. ARVIND. (The journal of contemporary issues in business and government, 2021)
Minimal intervention dentistry (MID) is a treatment philosophy that emphasizes the protection of existing tooth structure. It has been incorporated in dental curricula world wide in the management of dental caries. There is limited evidence that , whether the familiarity with MID principles inhibited through the curriculum is translated into clinical decision making and practice. The study was conducted to assess the knowledge,attitude,practice of general dental practitioners towards MID, registered dental practitioners in chennai formed the sampling frame. The data was analyzed using SPSS software and chi square tests were done between knowledge and attitude scores, knowledge scores and gender . 44.4% had good knowledge and 37.9% had good attitudes towards MID. General practitioners who had 5 to 10 years of clinical experience had 47.8% knowledge. Males had 39.1% good practice while females had 60.9% good practice . More of MID must be put into practice in the dental curriculum and implementing them during their clinical practice would ensure the proper knowledge and practice of dentists in future.